The good for nothing button - Willems, Mo.; Harper, Charise Mericle (New York : Hyperion Books for Children, 2017)
Elephant, who is cautious and pessimistic, and Piggie, who is optimistic and sometimes reckless, go outside to play in the sun and hope that it does not rain.
Booklist.
School Library Journal.
Wilson's Children.
Booklist, November 2008.
Bulletin (Center for Children's books), December 2008.
Horn Book, April 2009.
Keywords: Children Stories. -- Juvenile fiction; Friendship -- Juvenile fiction; Readers (Elementary).